Promoting access to medical technologies and innovation : intersections between public health, intellectual property and trade. (World Intellectual Property Organization (WIPO), 2022)
The coronavirus disease 2019 (COVID-19) pandemic constitutes an extraordinary global public health crisis that has created a pressing need for intensified global cooperation. This updated information note maps the myriad challenges posed by the outbreak in relation to the integrated health, trade and IP policy frameworks. It provides cross-references to the relevant sections in the updated trilateral study.